Soil-Transmitted Helminths Infection: the Severity Levels of Anemia and Concentration Levels in Bengkulu City (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2022)
Soil-Transmitted Helminths (STH) is a worm infection with a prevalence of 1.5 billion people worldwide and is mostly found in preschool and school children. Worm infection can affect the level of concentration and the quality of children's learning which results in less optimal achievement within their potential. The purpose of the research was to determine the correlation between STH infection and anemia and the level of concentration in children grades II-VI of elementary school in Kampung Melayu Sub-district, Bengkulu City. The research conducted using an analytic observational with the cross-sectional design. The research took 215 students as samples with a stratified random sampling method. Feces specimens were examined by using Kato-Katz technique. Haemoglobin levels were measured by using the POCT method and students' concentration levels were tested by using the Bourdon Vos Test. The results showed a significant relationship between STH infection with the occurrences of anemia (p = 0.001; RP = 0.225) and very weak correlation strength between STH infection with the concentration level (p = 0.014; RP = -0.167). Worm infection in preschool and school children can cause anemia and nutrition deficiency which affect their growth and development, cognitive function, concentration levels and learning achievement. Continuous education and coordination with related institutions is necessary to carry out strategies for preventing and treating worms thoroughly.